The structurally effect of surface coated rhamnogalacturonan I on response of the osteoblast‐like cell line SaOS‐2. Issue 6 (30th July 2013) - Svava, Rikke; Gurzawska, Katarzyna; Yihau, Yu; Haugshøj, Kenneth Brian; Dirscherl, Kai; Levery, Steven B.; Jørgensen, Niklas Rye; Gotfredsen, Klaus; Damager, Iben; Ulvskov, Peter; Jørgensen, Bodil
Abstract Osseointegration is important when implants are inserted into the bone and can be improved by biochemical surface coating of the implant. In this paper enzymatically modified rhamnogalacturonan I (RG‐I) from apple and lupin was used for biochemical coating of aminated surfaces and the importance of the quality of RG‐I, the nature of the binding, the fine structure of RG‐I, and its effect on SaOS‐2 cell line cultured on coated surfaces was investigated. SaOS‐2 cells are osteoblast‐like cells and a well‐established in vitro model of bone‐matrix forming osteoblasts. Purification by gel filtration could remove small fragments of galacturonic acid (GalA) and binding studies showed that the purity of the RG‐I molecules was important for the quality of the coating. The structure of RG‐I and osteoblast‐like cells' viability were positively correlated so that high content of 1, 4‐linked galactose (Gal) and a low content of arabinose in the RG‐I molecules favored cell viability. These results indicate that coating of implants with RG‐I affect osseointegration positively. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1961–1971, 2014.